A randomized double-blind phase II study evaluating the role of maintenance therapy with cabozantinib in high-grade uterine sarcoma after stabilization or response to doxorubicin ± ifosfamide following surgery or in metastatic first line treatment (EORTC62113). Issue 10 (15th October 2020) - Ray-Coquard, Isabelle; Hatcher, Helen; Bompas, Emmanuelle; Casado, Antonio; Westermann, Annekke; Isambert, Nicolas; Casali, Paolo Giovanni; Pratap, Sarah; Stark, Daniel; Valverde, Claudia; Anand, Anjana; Huizing, Manon; et al.
Abstract : Background: Uterine sarcomas are a group of rare tumors that include different subtypes. Patients with histopathological high-grade diseases are at high-risk of recurrence or progression, and have a poor prognosis. We aim to explore the most appropriate management in patients with uterine high-grade sarcomas. Primary objective: To assess the efficacy of maintenance treatment with cabozantinib in patients with high-grade uterine sarcomas who achieved clinical benefit after standard chemotherapy. Study hypothesis: Maintenance treatment with cabozantinib after standard chemotherapy given as an adjuvant treatment after curative surgery, or in locally advanced or metastatic disease, increases progression-free survival compared with placebo Trial design: This is a randomized double blinded phase II trial. Major inclusion/exclusion criteria: The study is enrolling adult patients with high-grade undifferentiated uterine sarcomas, high-grade endometrial stromal sarcomas, high-grade leiomyosarcoma, and high-grade adenosarcoma, FIGO (Federation International gynecologue Obstétricien) stage II/III to IV in stable disease or who achieved complete or partial response with doxorubicin ± ifosfamide, who are assigned 1:1 to 60 mg daily cabozantinib (experimental arm) or placebo (control arm), as maintenance therapy. Exclusion criteria include low-grade sarcoma. Primary endpoint: Progression-free survival at 4 months. Sample size: The study plans to enroll 90 patients to allow the randomization of 54 patients to detect an improvement in 4-month progression-free survival from 50% to 80% with 15% significance level and 85% power. Estimated dates for accrual completion: recruitment for the trial started in February 2015, and has currently enrolled 83 patients, of whom 35 patients have been randomized. The end of recruitment is anticipated for December 2020. Trial registration number: ClinicalTrials.gov, number NCT01979393 .